Data relating to "High resolution (cm scale) elevation data of Cockermouth Town, UK" - Mukherjee, Kriti; Rivas Casado, Monica; Ramachandran, Rakhee; Leinster, Paul (Cranfield University, 2024)
The project is focused on 'Harnessing long-term gridded rainfall data and microtopographic insights to characterise risk from surface water flooding'. The data provides the microtopography information of Cockermouth Town in England and the property resilience and resistance information. Three data sets are provided; 1.Elevation model at 25 cm resolution generated from lidar point clouds captured from aircraft; 2. Elevation model at 10 cm resolution generated from stereo photos captured by photographic cameras mounted on UAV; 3. shapefile having attributes related to flood resilience and resistance information for the residential buildings of Cockermouth Town.
Keywords: digital elevation model; shapefile